UNITEN delegates visit UMP - Shalfarina, Shahriman (2019)
A total of 22 Universiti Tenaga National (UNITEN) Library staff members attended a visit to the UMP Library and UMP Press on December 6, 2019. The UNITEN delegation was led by Head of e-Resources Unit, UNITEN Information Resources Centre, Mohd. Yazid Muji and welcomed by Acting Chief Librarian, Dzull Zabarrod Ahmad and UMP Press Director, Ts. Dr. Muhamad Mat Noor.